When 2nd generation biofuel meets water – The water solubility and phase stability issue. (1st December 2017) - Dechambre, Dominique; Thien, Julia; Bardow, André
Graphical abstract: Highlights: 2nd generation biofuels studied for mutual solubility with water. Water solubility in biofuels can drastically increase compared to Diesel. Increased solubility in water may impact environment. Phase behavior with water is key performance indicator for new biofuel blends. Abstract: Greenhouse gas emissions from the transportation sector could be reduced by using biofuels. To avoid competition with the food chain, second generation biofuels produced from lignocellulosic biomass are of major interest. The interaction of second generation biofuels and water needs to be studied since water is known to have major impacts for first generation biofuels. In this work, we explore the water solubility and phase stability for second generation biofuels from catalytic conversion of biomass. Tetrahydrofurans are potential biofuels for compression ignition engines. We find that the water solubility in tetrahydrofurans is increased by a factor 200 compared to Diesel. In furans, suitable as fuels for spark ignition engines, the water solubility is 4 orders of magnitude larger than in gasoline. In blends of biofuels, water solubility can either be increased or decreased depending on the blend component. Water can strongly influence the miscibility of biofuel-blends: adding small amounts of water to a γ-valerolactone – di- n -butyl ether blend leads to phase separation resulting in two organic phases with different combustion behavior. At the same time, the biofuels studied dissolve much better in water, which is relevant for potential environmental impacts. The phase behavior with water is thus shown to be an important key performance indicator for the development of biofuels.